If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(v-5)-2(v+3)=4
We move all terms to the left:
3(v-5)-2(v+3)-(4)=0
We multiply parentheses
3v-2v-15-6-4=0
We add all the numbers together, and all the variables
v-25=0
We move all terms containing v to the left, all other terms to the right
v=25
| x-(-41)=103 | | (11x-3)=(5x-9) | | (4x^2-1)(9x^2+49)=0 | | (-5+-3x)(3+-2x)=0 | | 10=z/3+9 | | 2x^2+6x=14 | | 16s^2-8s+1=0 | | ×-5y=17 | | 14=-12+5x-3x | | |4x-5|=2x-1 | | 2c/4+3c/2=1 | | 2n+10=—2+4n | | 5x+6x-10+x+5=180 | | 11×3p-7=6p+5-3p | | 9+2x1N=3x1N-2 | | 2x(x^2+2x-5)=0 | | -7d+d+-3d+2d=7 | | -2x+9-7x+9=27 | | 3d-2(-8+5d)=-3d-3d | | x+(-16)=-38 | | 5p5p=6p-2 | | 3+5p=6p+1-3p+6 | | —8—n=4—4n | | 1b-4+8b=21 | | -4=x5 | | 9.50n+1.25(3n+2)=68.75 | | -10x-15x-3x=8 | | -16=9x-7 | | -5x=16x-7 | | 9.50n+(1.25*3n)+2=68.75 | | 14=5+x/2 | | 244=14b+6 |